Maturação fenólica de uvas tintas cultivadas no Rio Grande do Sul - Sartori, Giliani Veloso (2011)
In the recent years, the concern about wines with better sensory characteristics and biological properties has motivated many studies on the phenolic compounds. The knowledge of ripening process of these substances is related to the necessity to produce high quality wines. In this study, red grape varieties VitisviniferaMalbec, Shiraz and Tannat were evaluated in relation to their phenolic ripeness. In the first two varieties, three harvest dates of a same vineyard were evaluated. In Tannat variety, one harvest date for three different vineyards was compared. All vineyards are situated in Rio Grande do Sul, Brazil, and they were studied in the crops of 2009/2010 and 2010/2011. The grape berries were evaluated in relation to the rate of skins, seeds, and pulps; and in relation to the industrial (pH, Brix and total acidity) and phenolic ripeness. For this last evaluation, 125 berries were crushed and macerated at pH 1.0 and pH 3.2 for 4 hours. Then, the following parameters were evaluated: extractability of anthocyanins (EA%), tannins in the skins (dpell%), tannins in the seeds (Mp%), total polyphenolic index (TPI 280), total anthocyanins (ApH1,0) and extractable anthocyanins (ApH3,2). Malbec and Shiraz varieties were micro-vinified by traditional method of red vinification, then the final wine was evaluated for its physic-chemical properties (pH and total acidity) and the content of phenolic compounds (IPT, total polyphenols, tannins, and anthocyanins). The analyses were performed in triplicate and statistically evaluated by the Tukey test at 5% of probability, by Principal Component Analysis (PCA) and by linear correlation. For Malbec variety, the outcomes showed a bigger industrial and phenolic ripeness (more Brix, less Total Acidity, more IPT, more content of anthocyanins and low values of Mp% and dpell%) to the 2010/2011 crop and later harvests. The Shiraz variety showed higher levels of total anthocyanins, extractable anthocyanins, and IPT in the second harvest date. The phenolic ripeness in the second crop was also higher for this variety, which had a higher extractability of anthocyanins (less EA%) and a great ripeness of tannins from the seeds and skins (lower Mp% and higher dpell%, respectively). For Tannat variety, the sample of Itaqui (warmer region) showed a higher content of anthocyanins and IPT in the first crop, which is similar to the sample of Dom Pedrito (less warmer region than Itaqui) in the following crop. In PCA, the samples were amounted by the influence of crop and the harvest date. The wine of both varieties presented higher levels of total phenolic, anthocyanins, and IPT in the vinification of later harvest and the crop of 2010/2011. The total polyphenol content, IPT 280, and the content of anthocyanins in wines were highly correlated with the rate of the industrial ripeness of the grape, content of extractable anthocyanins (ApH 3.2), tannin content in skins (Mp%). It is possible to conclude that later harvest can provide a grape with a higher phenolic ripeness. However, this ripeness is closely related and dependent on appropriate weather conditions of harvest.